FEATURES OF TWO-DIMENSIONAL SHEAR WAVE ELASTOGRAPHY DEPENDING ON MORPHOLOGICAL CHANGES IN CHRONIC VIRAL HEPATITIS C - Fazylov A.A; Nishanov D.A; Saipova G.G (Scholar Express Journals, 2022)
Clinical echographic and morphological analysis of the results of ultrasonic shear wave elastography (2D SWE) was performed in 44 patients with chronic viral hepatitis C (CVHC), verified by enzyme immunoassay. It has been established that in viral hepatitis C, depending on the morphological changes in the liver, there are dynamically increasing tendencies of inflammatory-dystrophic changes in the liver tissue. The results obtained are of practical importance in clarifying the stage of liver fibrosis according to the METAVIR scale and planning the treatment and rehabilitation of patients with CVHC.
Keywords: Chronic viral hepatitis C; shear wave elastography; Morphological changes in the liver